Tree Bark as Bioindicator for Heavy Metal Dispersal from Vehicular Emission - Sharina binti Sharan, Sharina (2011)
Repeating urbanization shows that the amount of vehicles is increasing day by day and contributes to the heavy metal contaminant to the atmosphere. The existence of heavy metal contaminant by vehicular emission in atmosphere has become one of the serious environmental issues.